2005
DOI: 10.1097/01.mlg.0000168111.11802.9c
|View full text |Cite
|
Sign up to set email alerts
|

Superantigens and Chronic Rhinosinusitis: Detection of Staphylococcal Exotoxins in Nasal Polyps

Abstract: The current study demonstrates the presence of superantigen toxins in 14 of 29 patients with CRSwNP, with SEB and TSST-1 being the most common. Further studies are necessary to correlate the presence of toxin with the pathological changes present in polyp tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 20 publications
6
101
2
3
Order By: Relevance
“…It was later demonstrated that at least 1 toxin was detected in 14 of 29 patients with bilateral CRSwNP, but in none of 11 healthy controls and in only 1 of 13 CRSsNP samples. 903 Serum SEA-specific, SEB-specific, and toxic shock syndrome toxin 1 (TSST-1)-specific IgE antibodies were detected in 0% vs 75% of healthy controls vs CRSwNP, respectively, and in about 60% of CRSwNP evidence of superantigen effects on the T cell receptor V-beta expansion in both CD4+ and CD8+ lymphocytes was noted. 904 The expansion of lymphocytes expressing T cell receptors with specific V beta-domains was limited to the polyp tissue, whereas much less bias was found in the blood.…”
Section: Viiib Crswnp: Comorbid Asthmamentioning
confidence: 99%
“…It was later demonstrated that at least 1 toxin was detected in 14 of 29 patients with bilateral CRSwNP, but in none of 11 healthy controls and in only 1 of 13 CRSsNP samples. 903 Serum SEA-specific, SEB-specific, and toxic shock syndrome toxin 1 (TSST-1)-specific IgE antibodies were detected in 0% vs 75% of healthy controls vs CRSwNP, respectively, and in about 60% of CRSwNP evidence of superantigen effects on the T cell receptor V-beta expansion in both CD4+ and CD8+ lymphocytes was noted. 904 The expansion of lymphocytes expressing T cell receptors with specific V beta-domains was limited to the polyp tissue, whereas much less bias was found in the blood.…”
Section: Viiib Crswnp: Comorbid Asthmamentioning
confidence: 99%
“…Согласно данным литературы, S. aureus является патогенной флорой и обладает выра-женным сенсибилизирующим свойством. Так-же известно, что токсины, полученные из зо-лотистого и эпидермального стафилококков, угнетают двигательную активность мерцатель-ного эпителия и затрудняет транспорт секрета; кроме того при воздействии золотистого ста-филококка наблюдается гемолиз эритроцитов [16]. 5550 (100-105 050) 900 000 (2100-1 020 000) = 0,040 Streptococcus spp.…”
Section: результатыunclassified
“…They have the ability to activate up to 30% of the T-cell population in contrast to the conventional antigen response, which activates only 0.01% of all T cells. In the acute setting superantigens may lead to the sudden and massive release of Th1 and Th2 cytokines which accounts for their acute toxicity (Llewelyn et al, 2002;Seiberling, Conley et al, 2005).…”
Section: Bacterial Superantigensmentioning
confidence: 99%
“…Patients with eosinophilic chronic rhinosinusitis remain the most refractory to medical and surgical intervention (Seiberling, Conley et al, 2005).…”
Section: Bacterial Superantigensmentioning
confidence: 99%